MOLECULAR-GENETIC APPROACH FOR OPTIMIZATION OF MODERN ANTIAGGREGANT THERAPY - N. YU. Knauer (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The targets of application of antiaggregant therapy by clopidogrel and the factors that influence its outcome were presented, in this review. Special attention was given to the application of personalized, approach for the optimization of clopidogrel therapy. The data of clinical investigations were discussed.